2012
DOI: 10.1017/s0272263112000691
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Semantic Transfer in Clitic Drop Among Simultaneous and Sequential Chinese-Spanish Bilinguals

Abstract: This study examines the acquisition of the featural constraints on clitic and null distribution in Spanish among simultaneous and sequential Chinese-Spanish bilinguals from Peru. A truth value judgment task targeted the referential meaning of null objects in a negation context. Objects were elicited via two clitic elicitation tasks that targeted anaphoric contexts and left-dislocated topics. An acceptability task tested sensitivity to left-dislocated object drop. Although simultaneous bilinguals were mostly un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 54 publications
(58 reference statements)
1
43
0
1
Order By: Relevance
“…A total of four tasks were implemented: a question-after-story task, a truthvalue judgment task, a sentence completion task and an acceptability judgment task. Cuza et al (2012) reported differential outcomes between child and adult immigrants when compared to native speaker controls: simultaneous bilinguals behaved in a consistently native-like manner across all tasks with the only exception their overextension of clitic use to [-definite, -specific] contexts, precisely where native speakers of Spanish do not allow them. The researchers claim that '[t]he morphosyntax of clitics seems in place among these early learners, but there appear to be gaps in their knowledge of the morphosemantic conditions on object drop, despite their intense exposure to Spanish in an immersion context.'…”
Section: The Null Object Phenomenon In L1 and L2 Acquisitionmentioning
confidence: 96%
See 1 more Smart Citation
“…A total of four tasks were implemented: a question-after-story task, a truthvalue judgment task, a sentence completion task and an acceptability judgment task. Cuza et al (2012) reported differential outcomes between child and adult immigrants when compared to native speaker controls: simultaneous bilinguals behaved in a consistently native-like manner across all tasks with the only exception their overextension of clitic use to [-definite, -specific] contexts, precisely where native speakers of Spanish do not allow them. The researchers claim that '[t]he morphosyntax of clitics seems in place among these early learners, but there appear to be gaps in their knowledge of the morphosemantic conditions on object drop, despite their intense exposure to Spanish in an immersion context.'…”
Section: The Null Object Phenomenon In L1 and L2 Acquisitionmentioning
confidence: 96%
“…Thus, Gundel, Stenson and Tarone (1984) and White (1996) study L1 English learners of L2 French; Zobl (1994) and Yuan (1997) study L1 Chinese learners of L2 English. L2 Spanish has been studied by Bruhn de Garavito and Guijarro-Fuentes (2002), Cuza, Pérez-Leroux and Sánchez (2012), Rothman and Iverson (2013) and Zyzik (2008), although the topic still needs further research to answer all relevant questions. However, to the best of our knowledge, object drop has not been investigated in third language (L3) acquisition, which is the area to which this article aims to contribute.…”
Section: Introductionmentioning
confidence: 99%
“…The short Spanish proficiency test was adapted from the cloze test section of the DELE version used in Cuza et al (2013). The biographic questionnaire and the oral narrative of the frog story based on the pictures were recorded.…”
Section: Instruments and Proceduresmentioning
confidence: 99%
“…In a comparison of production data with comprehension (TVJ), Grüter (2006) demonstrated that L2 production errors are more a function of processing overload than of deficient grammatical knowledge because the learners' responses on the TVJ were far more accurate than their clitic production. Indeed, some studies have shown that the most frequent error is not the use of in situ pronouns, but pronoun omission (Cuza et al, 2013;Grüter, 2006;Grüter & Crago, 2012;Herschensohn, 2004).…”
Section: Current Studymentioning
confidence: 99%
“…More recently, studies have used elicited production, offline judgment tasks (e.g., Grammaticality Judgment (GJ), Truth Value Judgment (TVJ)), comprehension checks and translation (Cuza et al 2013;Grüter, 2006;Grüter & Crago, 2012). These measures do not provide insight, however, into the learner's tacit, online knowledge of the grammar of pronouns.…”
Section: Introductionmentioning
confidence: 99%